Coping styles moderate the relationship between perceived discrimination and eating behaviors during the transition to college. (1st January 2022) - Lee, Sharon Y.; Agocha, V. Bede; Hernandez, Paul R.; Park, Crystal L.; Williams, Michelle; Carney, Lauren M.
Abstract: The transition to college is a critical developmental window during which eating behaviors are susceptible to dysregulation. Changes in exposure to discrimination contribute to alterations in eating behaviors, which may be exacerbated or attenuated by coping styles. The present longitudinal study examines whether increases in perceived discrimination predict increases in overeating and decreases in eating well during the transition to college. We expect that adaptive coping styles will buffer against, while maladaptive coping styles will exacerbate, the effects of increases in perceived discrimination on increases in overeating and decreases in eating well. First year students (n = 804) were assessed at two time points: the spring before freshman year (Time 1) and one year later during the spring semester of freshman year (Time 2). Two distinct coping styles emerged from a factor analysis: adaptive (active coping, planning, emotional support, positive reframing, acceptance, instrumental support) and maladaptive coping (denial, venting, self-blame, self-distraction). Increases in perceived discrimination, lower adaptive coping, and higher maladaptive coping had main effects for predicting more overeating at Time 2. Among students who reported increases in perceived discrimination, higher use of adaptive coping was associated with less overeating at Time 2 while higher use of maladaptive coping was associated with more overeating. While adaptive and maladaptive coping styles had main effects on eating well, change in perceived discrimination did not. Neither adaptive nor maladaptive coping styles interacted with change in perceived discrimination to predict eating well. Findings inform a gap in the literature about the relationship between discrimination and eating behaviors from a developmental perspective by demonstrating that adaptive and maladaptive coping styles influence the effects of changes in perceived discrimination on overeating during the college transition.